Gianni Celati: the ‘flâneur’ in the digital age. In search of the small oasis - Nicolò Marangoni (Griseldaonline)
Following Rilke’s attitude in his Duino Elegies, Gianni Celati moves toward the frontiers of negation, recognizing that all things have a limit (mourning), however, at this «edge of no», he suggests that things balance upon a hidden foundation (silence). Thus, negation is not exclusively death, and the flâneur, standing at this limit, as a Wanderer, rediscovers the small oasis, that is, the word. In this wandering, Celati displays a particular inclination toward the search for and discovery of that unknown second meaning of things and places. A possible and productive analysis of Celati’s works may be conceived by approaching his texts through Heidegger’s hermeneutics. The chosen interpretative effort is not without its challenges. However, it is certainly useful for the restoration of that ethical/aesthetic and ecological flânerie to the present that now more than ever is relevant in an era so fleeting and digital, where paths disappear too easily and horizons are equally erased.